2014
DOI: 10.1002/ange.201408015
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin‐Based Fluorogenic Probes for No‐Wash Protein Labeling

Abstract: A fluorescent protein‐labeling strategy was developed in which a protein of interest (POI) is genetically tagged with a short peptide sequence presenting two Cys residues that can selectively react with synthetic fluorogenic reagents. These fluorogens comprise a fluorophore and two maleimide groups that quench fluorescence until they both undergo thiol addition during the labeling reaction. Novel fluorogens were prepared and kinetically characterized to demonstrate the importance of a methoxy substituent on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…FlAsH was able to selectively react with a short 15 amino acid polypeptide tag containing a tetracysteine motif (CCXXCC). [122] Vibrational deactivation or PET by the As-1,2-ethanedithiol groups are supposed to be (44), [129] dansyl (45), [130]or coumarin (46)(47)(48), [131] based bis-maleimides ( Figure 25). The PET process accused with the quenching phenomenon allows 7-350-fold enhancement upon Michael addition with Cys2 motifs.…”
Section: Azide-bearing Fluorogenic Dyesmentioning
confidence: 99%
“…FlAsH was able to selectively react with a short 15 amino acid polypeptide tag containing a tetracysteine motif (CCXXCC). [122] Vibrational deactivation or PET by the As-1,2-ethanedithiol groups are supposed to be (44), [129] dansyl (45), [130]or coumarin (46)(47)(48), [131] based bis-maleimides ( Figure 25). The PET process accused with the quenching phenomenon allows 7-350-fold enhancement upon Michael addition with Cys2 motifs.…”
Section: Azide-bearing Fluorogenic Dyesmentioning
confidence: 99%
“…Over the past several years, fluorescent chemosensors have been developed as useful sensors for various metal ions due to their simplicity, specificity and sensitivity monitoring with a fast response time [27][28][29]. Therefore, various fluorophores with different excitation and emission wavelengths, such as coumarin [30,31], pyrene [32,33], 1, 8-naphthalimide [34,35], xanthenes [36,37], squaraine [38], cyanine [39], boron dipyrromethene difluoride (BODIPY) [40], and nitrobenzofurazan [41], have been employed to develop various chemical sensors. Among the developed fluorophores, rhodamine and its derivatives [42,43] employ an ideal framework in the construction of fluorescent probes due to their excellent spectroscopic properties including high fluorescence quantum yield, large molar extinction coefficient, and visible wavelength excitation [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown how substituents on the maleimide ring can attenuate its reactivity, 13 and have applied this information to the design of selective protein labeling agents. 14 However, the mechanism of the addition reaction has still not been completely elucidated. Although early work 9,15−21 showed that this reaction is faster at higher pH, we still had questions regarding whether the addition reaction occurred in a stepwise or a concerted fashion, and whether the reaction at a given pH would be faster with a more nucleophilic thiol (having a higher pK a ) or a higher proportion of thiolate from a more acidic thiol (having a lower pK a ).…”
Section: ■ Introductionmentioning
confidence: 99%